Identifikasi dan Uji Aktivitas Antimikroba Senyawa Kimia Fraksi Air Buah Leunca (Solanum Nigrum L.) - Afni Panggar Besi; Devy Octarina; Aprianto Aprianto (Jurnal Ventilator, 2023)
This study was conducted to determine the antimicrobial effectiveness of chemical compounds from the water fraction of leunca fruit. Leunca fruit extract was obtained by maceration, then the results of maceration were evaporated and then fractionated. Antimicrobial activity testing was carried out using the agar diffusion method against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Candida albicans ATCC 01231. The concentration variations of leunca fruit water fraction used were 10%, 20%, 30%, 40%, and 50%. The results of the antimicrobial activity test of leunca fruit water fraction compounds obtained the average inhibition diameter of Staphylococcus aureus ATCC 25923 microbes respectively 7.5 mm; 8.3 mm; 8.8 mm; 9.5 mm; and 10.4 mm. On the microbe Escherichia coli ATCC 25922 consecutively 7.8 mm; 8.1 mm; 9.3 mm; 10 mm; and 11.4 mm. while on the microbe Candida albicans ATCC 01231 the diameter of the bland chemical compound of leunca fruit water fraction is only found in the 50% concentration variation with an average inhibition diameter of 9.1 mm. Based on the results obtained, it can be concluded that the water fraction of leunca fruit (Solanum Nigrum L.) has activity as an antimicrobial against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Candida albicans ATCC 01231 with the largest inhibition zone diameter shown in the 50% concentration variation.